Trends in Antimicrobial Resistance of Canine Otitis Pathogens in the Iberian Peninsula (2010–2021) - Biel Garcias; Mar Batalla; Anna Vidal; Inma Durán; Laila Darwich (Antibiotics)
Background: The close relationship between humans and petsraises health concerns due to the potential transmission of antimicrobial-resistant (AMR) bacteria and genes. Bacterial otitis is an emerging health problem in dogs, given its widespread prevalence and impact on animal welfare. Early detection of resistance is vital in veterinary medicine to anticipate future treatment challenges. Objective: This study aimed to determine the prevalence of AMR bacteria involved in 12,498 cases of otitis in dogs from the Iberian Peninsula and the evolution of AMR patterns over an 11-year period. Methods: Data was provided by the Veterinary Medicine Department of a large private diagnostic laboratory in Barcelona. Antimicrobial susceptibility testing was performed using the standard disk diffusion method and minimum inhibitory concentration (MIC) testing. Results: The frequency of the principal bacterial agents was 35% Staphylococcus spp. (principally S. pseudointermedius), 20% Pseudomonas spp. (P. aeruginosa), 13% Streptococcus spp. (S. canis), and 11% Enterobacterales (Escherichia coli and Proteus mirabilis). Antimicrobial susceptibility testing revealed P. aeruginosa (among Gram-negatives) and Enterococcus faecalis (among Gram-positives) as the species with the highest AMR to multiple antimicrobial classes throughout the years. According to the frequency and time evolution of multidrug resistance (MDR), Gram-negative bacteria like P. mirabilis (33%) and E. coli (25%) presented higher MDR rates compared to Gram-positive strains like Corynebacterium (7%) and Enterococcus (5%). The AMR evolution also showed an increase in resistance patterns in Proteus spp. to doxycycline and Streptococcus spp. to amikacin. Conclusions: This information can be useful for clinicians, particularly in this region, to make rational antimicrobial use decisions, especially when empirical treatment is common in companion animal veterinary medicine. In summary, improving treatment guidelines is a key strategy for safeguarding both animal and human health, reinforcing the One Health approach.